Effect of Mixing on a Lab-Scale Bioreactor Productivity - Liew, Emily; Nandong, Jobrun; Samyudia, Yudi (Engineers Australia, 2009)
In this paper, we study the impact of variable mixing conditions arising from the different sets of aeration rate and stirrer speed on the ethanolic fermentation process, which utilizes the hydrolyzed cassava starch as carbon source. Interestingly, over the ranges of aeration rate and stirrer speed used in the study, the ethanol yield varied from 10% to 85% of theoretical maximum yield. Additionally over these experimental conditions, the selectivity of ethanol over glycerol varied from 3.6 to 12.3. One conclusion that can be drawn from this experimental study is that, the large variations in yield, selectivity and ethanol formation rate were more likely due to the different mixing conditions resulting from different values of aeration rate and stirrer speed, and less likely due to glucose and growth rates as previously reported.